2003
DOI: 10.1152/jn.01085.2002
|View full text |Cite
|
Sign up to set email alerts
|

New Corticocuneate Cellular Mechanisms Underlying the Modulation of Cutaneous Ascending Transmission in Anesthetized Cats

Abstract: The ascending cutaneous transmission through the middle cuneate nucleus is subject to cortico-feedback modulation. This work studied the intracuneate cellular mechanisms underlying the corticocuneate influence. Single unit extracellular records combined with iontophoresis showed that the corticocuneate input activates cuneo-lemniscal (CL) and noncuneo-lemniscal (nCL) cells via N-methyl-D-aspartate (NMDA) and non-NMDA receptors as shown by the decrease of the cortical-induced activation on ejection of CNQX and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 61 publications
6
45
0
Order By: Relevance
“…The ML antidromic latencies of the 188 proprioceptive neurons were compared with the antidromic latencies of a different sample of 261 CL cells with cutaneous receptive fields recorded more dorsally, in the cluster region of the medial cuneate nucleus, in previous work from our laboratory (Aguilar et al, 2002(Aguilar et al, , 2003Soto et al, 2004Soto et al, , 2006. The antidromic latencies of these samples were significantly different ( p Ͻ 0.001, Mann-Whitney).…”
Section: Medial Lemniscus Nrgc Mlr and Dorsal Columnmentioning
confidence: 96%
See 2 more Smart Citations
“…The ML antidromic latencies of the 188 proprioceptive neurons were compared with the antidromic latencies of a different sample of 261 CL cells with cutaneous receptive fields recorded more dorsally, in the cluster region of the medial cuneate nucleus, in previous work from our laboratory (Aguilar et al, 2002(Aguilar et al, , 2003Soto et al, 2004Soto et al, , 2006. The antidromic latencies of these samples were significantly different ( p Ͻ 0.001, Mann-Whitney).…”
Section: Medial Lemniscus Nrgc Mlr and Dorsal Columnmentioning
confidence: 96%
“…3A-C, for proprioceptive cells). Table 2 shows some of the distinctive properties of cutaneous and proprioceptive neurons at the middle main cuneate nucleus derived from the present and previous work (Aguilar et al, 2003).…”
Section: Medial Lemniscus Nrgc Mlr and Dorsal Columnmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been reported that the sensorimotor cortex exerts a selective control of the somatosensory transmission at the DCN (Aguilar et al 2003;Canedo and Aguilar 2000;Nuñez 1998, 2004). Indeed, the corticofugal input facilitates sensory responses of gracile neurons with overlapping receptive fields and inhibits sensory responses of cells with separate receptive fields, probably providing a synaptic mechanism for the enhancement of contrast between sensory signals.…”
Section: Introductionmentioning
confidence: 99%
“…The wavelet transform has been used to analyze brain signals from the very beginning in neuroscience. Most of its applications are in electroencephalographic recordings (see e.g., Alegre et al 2003;Castellanos and Makarov 2006;Goelz et al 2000;Mäkinen et al 2004;Mormann et al 2005;Murata 2005;Quiroga and Garcia 2003;Schiff et al 1994). However, there are few studies on synchronization between pairs of spike trains (e.g., stimulus-neural response).…”
Section: Introductionmentioning
confidence: 99%